2020
DOI: 10.3390/ijms21020680
|View full text |Cite
|
Sign up to set email alerts
|

Genome and Karyotype Reorganization after Whole Genome Duplication in Free-Living Flatworms of the Genus Macrostomum

Abstract: The genus Macrostomum represents a diverse group of rhabditophoran flatworms with >200 species occurring around the world. Earlier we uncovered karyotype instability linked to hidden polyploidy in both M. lignano (2n = 8) and its sibling species M. janickei (2n = 10), prompting interest in the karyotype organization of close relatives. In this study, we investigated chromosome organization in two recently described and closely related Macrostomum species, M. mirumnovem and M. cliftonensis, and explored kary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(67 citation statements)
references
References 58 publications
2
65
0
Order By: Relevance
“…Moreover, primarily due to the discovery of a whole-genome duplication and accompanying karyotype instability in M. lignano (Zadesenets et al 2016, 2017), there is increased interest in expanding the genomic resources and molecular phylogenetic placement of additional species in the genus,. To this end, recent work has provided transcriptomic resources for additional species (Brand et al 2020) and field-collections have revealed similar karyological rearrangements to the ones observed in M. lignano in some closely related species, while others were found to have stable diploid genomes (Schärer et al 2020; Zadesenets et al 2020). Accurate phylogenetic information will greatly help guide the search for additional Macrostomum model species and permit to study the (co)evolution of the large diversity of morphological and behavioural traits in the genus, a brief introduction of which we provide in the following.…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, primarily due to the discovery of a whole-genome duplication and accompanying karyotype instability in M. lignano (Zadesenets et al 2016, 2017), there is increased interest in expanding the genomic resources and molecular phylogenetic placement of additional species in the genus,. To this end, recent work has provided transcriptomic resources for additional species (Brand et al 2020) and field-collections have revealed similar karyological rearrangements to the ones observed in M. lignano in some closely related species, while others were found to have stable diploid genomes (Schärer et al 2020; Zadesenets et al 2020). Accurate phylogenetic information will greatly help guide the search for additional Macrostomum model species and permit to study the (co)evolution of the large diversity of morphological and behavioural traits in the genus, a brief introduction of which we provide in the following.…”
Section: Introductionmentioning
confidence: 78%
“…Besides the SD and TD, the M. lignano-specific hidden tetraploidy may be the main mechanism of this species-specific gene duplication. Recent studies have showed that hidden tetraploidy may occur in the M. lignano genome with ∼75% of the sequence containing repeats and transposon sequences, potentially suggesting wholegenome duplication or more recent large segmental duplications (Wasik et al, 2015;Zadesenets et al, 2017Zadesenets et al, , 2020. Thus, we presume that polyploidy, SD, and TD are the main mechanisms driving the extensive expansion of the NR gene family in M. lignano.…”
Section: Extensive Expansion Of Nr Family In M Lignanomentioning
confidence: 75%
“…Deviations from full inheritance of the GFP marker may be due to karyotype polymorphism observed in M. lignano (Zadesenets et al. 2016, 2017, 2020). But here, we used a GFP(+) BAS1 culture in which karyotype polymorphism and heterozygosity was deliberately reduced (Vellnow et al.…”
Section: Methodsmentioning
confidence: 99%